PENGARUH GROWTH, FIRM SIZE, PROFITABILITY DAN BUSINESS RISK TERHADAP STRUKTUR MODAL PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2011-2014 - Titik Fauziah, 12.05.51.0167; Sudiyatno, Bambang (Students Journal of Economic and Management, 2016)
The capital structure has a very important function in the operation of the company. Changes in capital structure will bring changes to profit in the future. The purpose of the study was to examine how the effect of growth, firm size, business risk and profitability of the capital structure of the companies listed in the Indonesia Stock Exchange. This study used a sample of companies listed on the Indonesia Stock Exchange. Based on the observations, the number of companies listed on the Indonesia Stock Exchange during the study period between the years 2011-2014 was 38 companies for 4 years as many as 138 data. Methods of research data analysis using linear regression. The test results showed that growth, business risk significant negative effectÂ  onÂ  the capital structure in manufacturing companies on the Stock Exchange, firm size positive and significant impact on the capital structure in manufacturing companies on the Stock Exchange, and profitability have negative effect and significant impact on the capital structure of the manufacturing companies in the Stock Exchange. Keywords: growth, firm size, business risk, profitability and capital structure.